Five-year changes of somatic risk factors and comorbidities in patients with angina of effort - Р. О. Ugurchieva; R. Т. Didigova; M. B. Khudyakov; M. N. Mamedov (Российский кардиологический журнал, 2020)
Aim. To assess five-year changes of somatic risk factors and comorbidities in patients with angina of effort.Material and methods. The study included 320 patients (143 men and 177 women aged 40-69 years) with coronary artery disease (CAD), class I-III angina of effort. Patients underwent examinations in 2012 in three medical centers of the Republic of Ingushetia (Russia), and in 2017 they were invited for a second complex examination with questionnaires, biochemical analysis, and instrumentation.Results. Over the five-year follow-up, there was an increase of men with class III effort angina up to 45%; a similar trend was observed in women. Both men and women experienced a three-fold increase in the incidence of type 2 diabetes. Initially and during the follow-up, chronic obstructive pulmonary disease was diagnosed 2 times more often in men than in women, which may be associated with smoking. A small increase in the total cholesterol level was recorded in the cohort; among women, these changes were significant. Target levels reach no more than 20% of patients. A significant increase of blood glucose levels over the 5-year period was observed in a cohort of men and women with effort angina.Conclusion. Over the 5-year follow-up, there was a clinical deterioration of the effort angina, which is associated with an increase in the incidence of some somatic diseases and the severity of the main behavioral and biological risk factors.